Software Design Baseado em Subsistemas Autônomos - Focalizando o Reuso - Sanchez, Maria Luiza d’Almeida; Maffeo, Bruno (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1996: Anais do X Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.1996.24449, 1996)
This work focus on reuse features of a design method for real-time process-control systems. The method is based on "Information Hiding and Exchange of Messages between Independent Subsystems". It employs information hiding and concepts inherited from development techniques using Configuration Languages. It allows the partition of a complex system into more manageable subsystems intended for reuse in other systems that have to perform similar functions.